Enriching Efl Learners’ Vocabulary Through Word Wall For Seventh Grade at SMPN 3 Abab - Yesin Erlin; Nike Angraini; Jaya Nur Iman (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Students around the world often face challenges in expanding their vocabulary in a second or foreign language. Common obstacles include understanding complex vocabulary, difficulty in pronunciation, and difficulty remembering new words. Cultural factors, learning environment, and teaching methods can also affect students' vocabulary acquisition. Vocabulary is one of the aspects present in most language skills such as listening, speaking, reading, and writing when learning English as a second language. In this study, the researcher employed this design to evaluate the effectiveness of the "word wall" strategy in enhancing students' vocabulary achievement. An experimental and a control group were formed, both of which underwent pre-tests and post-tests. This study used a quasi-experimental design, categorized as such due to the comparison between the group using the "word wall" strategy and the conventional group. The primary objective of this study was to evaluate the effectiveness of the "word wall" strategy in improving students' vocabulary mastery. There were 27 students in the experimental group. Based on the data analysis, the researcher concluded that the use of "word wall" had a significant enrichment on students' vocabulary mastery. This finding was supported by the results of the t-test, which showed that the average post-test score of students in the experimental class (78.79) was higher than the pre-test score (59.53), with a difference of 19.26. The t-test results showed significance with p<0.05, specifically p<0.001, indicating that the alternative hypothesis (Ha) was accepted. Additionally, the implementation of "word wall" also had a positive impact on students' attitudes toward the teaching and learning activities. When the teacher used "word wall" during instruction, students appeared more interested and motivated to learn.